Computed Tomography Angiography Assessment of Acute Aortic Syndromes: Classification, Differentiating Imaging Features, and Imaging Interpretation Pitfalls. Issue 1 (February 2022) - Modares, Mana; Hanneman, Kate; Ouzounian, Maral; Chung, Jennifer; Nguyen, Elsie T.
An acute aortic syndrome (AAS) is an important life-threatening condition that requires early detection and management. Acute intramural hematoma (IMH), aortic dissection (AD) and penetrating atherosclerotic ulcer (PAU) are included in AAS. ADs can be classified using the well-known Stanford or DeBakey classification systems. However, these classification systems omit description of arch dissections, anatomic variants, and morphologic features that impact outcome. The Society for Vascular Surgery and Society of Thoracic Surgeons (SVS-STS) have recently introduced a classification system that classifies ADs according to the location of the entry tear (primary intimomedial tear, PIT) and the proximal and distal extent of involvement, but does not include description of all morphologic features that may have diagnostic and prognostic significance. This review describes these classification systems for ADs and other AAS entities as well as their limitations. Typical computed tomography angiography (CTA) imaging appearance and differentiating features of ADs, limited intimal tears (LITs), IMHs, intramural blood pools (IBPs), ulcer-like projections (ULPs), and PAUs will be discussed. Furthermore, this review highlights common imaging interpretation pitfalls, what should be included in a comprehensive CTA report, and provides a brief overview of current management options.